2021
DOI: 10.1021/acsanm.1c02550
|View full text |Cite
|
Sign up to set email alerts
|

Nanofabrication via Maskless Localized Atomic Layer Deposition of Patterned Nanoscale Metal Oxide Films

Abstract: A modified open-air spatial atomic layer deposition (SALD) head is employed to fabricate complex oxide patterns on various substrates. The coreactant being kept in the surrounding atmosphere, a simple injection head that consists of three concentric nozzles with only one precursor outlet has been designed. Easy and reversible modification in the diameter of the metal precursor outlet permits direct patterning with different lateral sizes. Maskless deposition of uniform and homogenous TiO 2 and ZrO 2 thin films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Muñoz-Rojas’ team has, for example, shown that a head based on concentric channels can be used to deposit free-from patterns with resolution in x-y in the order of the cm . Other teams have later shown that it is possible to reach micrometric resolution. , In fact, SALD/CVD approaches offer a huge potential for the fast fabrication of miniaturized complex patterns at a high rate with reduced energy demands. , …”
Section: Overview and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muñoz-Rojas’ team has, for example, shown that a head based on concentric channels can be used to deposit free-from patterns with resolution in x-y in the order of the cm . Other teams have later shown that it is possible to reach micrometric resolution. , In fact, SALD/CVD approaches offer a huge potential for the fast fabrication of miniaturized complex patterns at a high rate with reduced energy demands. , …”
Section: Overview and Discussionmentioning
confidence: 99%
“…135,136 In fact, SALD/ CVD approaches offer a huge potential for the fast fabrication of miniaturized complex patterns at a high rate with reduced energy demands. 128,137 As discussed in section 2.4,, both modeling and in situ characterization are powerful tools to optimize the amount of precursor injected. Modeling has already been extensively used to optimize different SALD processes 132,138−145 and could be readily applied toward the optimization of precursor utilization.…”
Section: High Throughput Processes Eg Spatial Aldmentioning
confidence: 99%
“…29,72 More recently, researchers have demonstrated the possibility to direct surface patterning via a simple versatile miniaturized open-air s-ALD head, which is developed by additive manufacturing. 71,73,76 With such a technique, true direct printing of complex patterns with a lateral resolution of submillimeters is successfully achieved in a miniaturized nozzle. One example is the ATLANT3D™ technology developed by ATLANT3D.…”
Section: Applications Of S-aldmentioning
confidence: 99%
“…Here again, the resolution of the obtained patterns in X-Y depends on the head design and the possibility to scale it down. Indeed, the latter work by Midani et al presented a similar concept in which sub-millimiter resolution was achieved by inserting a capillary in the central metal precursor channel of the SALD pen [45].…”
Section: (D) Comsol Simulation Of the Mass Fraction Of Each Precursor...mentioning
confidence: 99%